2023
DOI: 10.1162/neco_a_01571
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Neuronal Dynamics Is Learned by Gradient Descent for Temporal Processing Tasks

Abstract: Individual neurons in the brain have complex intrinsic dynamics that are highly diverse. We hypothesize that the complex dynamics produced by networks of complex and heterogeneous neurons may contribute to the brain's ability to process and respond to temporally complex data. To study the role of complex and heterogeneous neuronal dynamics in network computation, we develop a rate-based neuronal model, the generalized-leaky-integrate-and-fire-rate (GLIFR) model, which is a rate equivalent of the generalized-le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This hypothesis is an extension of recent studies that found that the performance of neural networks on various classification and function approximation tasks could be improved by allowing for heterogeneous neuron parameters ( 79 81 ). Our work extends these findings by demonstrating that whether more homogeneous or more heterogeneous networks are computationally beneficial differs between encoding and signal transformation tasks.…”
Section: Discussionmentioning
confidence: 74%
“…This hypothesis is an extension of recent studies that found that the performance of neural networks on various classification and function approximation tasks could be improved by allowing for heterogeneous neuron parameters ( 79 81 ). Our work extends these findings by demonstrating that whether more homogeneous or more heterogeneous networks are computationally beneficial differs between encoding and signal transformation tasks.…”
Section: Discussionmentioning
confidence: 74%